Education and the good life: Petrarch’s insights and the current research on well-being - Radenovic, Ljiljana (Journal of beliefs and values, 2021)
According to Petrarch, the main goal of the liberal arts is to help us live a good life and become wise, virtuous, and serene. This is also something achieved via true Christian faith. In this paper, my goal is twofold. First, I review Petrarch’s general attitude to the good life and the ways to live it, along with his advice on how to remain content or regain peace in the face of difficulties. As a devout Christian, Petrarch emphasises that faith suffices for a person to have a virtuous and contented life, but the combination of a liberal arts education and a Christian education is ideal. Second, I highlight the importance of Petrarch’s insights, by taking a closer look at the contemporary research on the universal psychological needs and how their satisfaction relates to the overall sense of well-being of people across different cultures. Studies show that people who feel more autonomous generally have an increased sense of well-being. Furthermore, those who are ‘mindful’, that is those who can precisely identify their own psychological states and the situation they are in, tend to feel more autonomous. I place Petrarch’s insistence that an education combining the liberal arts and religion helps us become serene and peaceful within the context of these results. I call for further research on the relations between autonomy, mindfulness, and education and show that some centuries-old insights can direct our research and, as such, prove valuable today.